Tracking the religious transformation in the early Medieval Eastern Caucasus - Aliyeva, Lala A. (Journal of the Belarusian State University. History, 2025)
The author of the article studies the religious transformation in the early Medieval Eastern Caucasus, mostly in the territories of contemporary Republic of Azerbaijan, by the thorough analysis of the historical chronicles and other written sources. Muslim historians and geographers works, Armenian and Georgian chronicles are interpretated and combined. The article embarks upon a comprehensive research, unraveling gradual religious transformation in the region.
Keywords: Azerbaijan; Eastern Caucasus; Christianity; Zoroastrianism; Judaism; Islam; Arab conquest; religious transformation